Effectiveness of Deep Brain Stimulation (DBS) in the Anterior Thalamic Nucleus (ATN) for Drug-Resistant Epilepsy: A Comprehensive Literature Review - Hidayat, Yoga Arif; Monika, Caroline; Rusli, Bryant Agustino; Ramadhan, Irfan Fadillah; Purnomo, Athaya Febriantyo (GLOBAL HEALTH SCIENCE GROUP, 2024)
Epilepsy, a chronic neurological disorder characterized by recurrent seizures, significantly impacts the lives of millions worldwide. While antiepileptic drugs have become the standard of care for seizure control, a substantial portion of epilepsy patients, estimated at approximately one-third, continues to experience seizures despite trying multiple medications. Consequently, there is a pressing need to explore alternative and more effective treatment options. This study was conducted to review more deeply Deep Brain Stimulation (DBS) has emerged as a promising intervention for individuals with drug-resistant epilepsy. DBS entails the implantation of small electrodes into specific brain regions to provide controlled electrical stimulation, aiming to modulate abnormal neural activity associated with seizures. Among the targeted brain regions, the Anterior Thalamic Nucleus (ATN) has garnered substantial attention due to its potential to reduce seizure frequency in individuals for whom conventional therapies have proven inadequate. A literature search was conducted from journal articles using databases in the form of Pubmed, Medline, Google Scholar, Proquest, Embase, SAGE, and Web of Science. The search strategy involved using a set of keywords and their synonyms without any publication date restrictions. In this comprehensive review, the effectiveness of DBS in the ATN for drug-resistant epilepsy is critically examined. Notably, recent clinical trials have shown significant promise. For instance, the SANTE (Stimulation of Anterior Nucleus of Thalamus for Epilepsy) study demonstrated that, after three months, 110 drug-resistant epilepsy patients receiving DBS in the ATN experienced a remarkable 40% reduction in seizure frequency. Long-term follow-up revealed progressive improvements, with a subsequent 69% decrease in seizure frequency over five years. There is potential adverse events associated with DBS, including bledding, infections, paresthesia, moving disorder and psychiatric disorder. DBS is highly effective in reducing seizure frequency, controlling seizures, and improving the patient’s quality of life. DBS can also serve as a treatment option for various other neurological disorders. In the future it is expected to become more effective with advances in neuroscience, particularly neurointerventions, which allow more precise anatomical targeting. Monitoring possible side effects caused by DBS is critical to optimizing patient outcomes. In conclusion, this review underscores the potential of DBS in the ATN as an effective therapy for drug-resistant epilepsy. While significant progress has been made, further research is needed to refine treatment parameters, enhance patient selection, and evaluate long-term outcomes. DBS represents a beacon of hope for individuals whose lives are profoundly affected by drug-resistant epilepsy, offering the prospect of improved seizure control and enhanced quality of life.